PENINGKATAN HASIL BELAJAR ILMU PENGETAHUAN ALAM DENGAN PENERAPAN METODE DEMONSTRASI SISWA KELAS V SD NEGERI 014 BERINGIN MAKMUR KECAMATAN KERUMUTAN - Kamril ' (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2016)
The background of this study is the low student learning outcomes SDN 014 IPA BeringinMakmur. Of the 25 students only 12 students (48%), which reached the KKM. For PTK wasperformed by applying motode demonstration. This study was conducted twice. This studyfocuses on the results of students learn science. This is evidenced by the results of learningscience students has increased at each cycle. At the beginning of the learning outcomes IPAscore scored an average of 65 to 50% the percentage of completeness. In the first cycle oflearning outcomes IPA value gained 69.25 with the percentage of completeness 67%, thesecond cycle obtain an average value of 74.5 to 85% the percentage of completeness.